Salicylic acid mediated metabolite elicitation and growth responses in long pepper (Piper longum L.) - Krishna Veni Harish (Department of Plantation Crops and Spices, College of Agriculture, 2019)
A study on “Salicylic acid mediated metabolite elicitation and growth responses in long pepper (Piper longum L.)” was carried out at the Department of Plantation Crops and Spices, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala during 2017-19. The study aimed at assessing the effect of different concentrations of salicylic acid on plant growth, yield and metabolite production in P. longum. The rooted cuttings from the promising variety of long pepper, Viswam plants were exposed to nine foliar spray treatments with varying salicylic acid (SA) concentrations and control treatments viz, SA 0.1 mM (T1), SA 0.5 mM (T2), SA 1.0 mM (T3), SA 1.5 mM (T4), SA 2.0 mM (T5), SA 2.5 mM (T6), ethanol (0.20 per cent) spray (T7), water spray (T8) and control (T9) at 2, 4 and 6 months after planting (MAP). The study was conducted in completely randomized block design (CRD) with three replications. The plant growth parameters, metabolite production, physiological parameters, yield parameters and major nutrient uptake in response to various foliar spray treatments were studied. The plant growth parameters viz., plant height, number of leaves, leaf area, number of primary branches, number of spike bearing branches and shoot weight per plant (fresh and dry weight) were recorded at 3, 5 and 7 MAP. The foliar treatment with SA 0.1 mM (T1) recorded significantly higher values with respect to plant height, number of leaves, leaf area and shoot weight at all stages of observation. All these parameters showed a decreasing trend with increasing concentration of SA. However, no significant variation among the treatments was observed with respect to the number of primary branches and spike bearing branches. The days to emergence of spike and to flowering varied significantly among the treatments tried. SA 0.1 mM (T1) showed earliness with respect to spike emergence (75 days) and flowering (22.67 days). However, the higher concentration took more number of days to emergence of spike (84.67 days) and to flowering (27 days), which was found to be on par with the foliar spray treatments devoid of SA. However, the days from emergence to maturity of spike did not show any significant variation among the treatments. The plant metabolites, viz., total chlorophyll, total proteins and defense enzymes (peroxidase, catalase and superoxide dismutase) at 3, 5 and 7 MAP, recorded significantly higher values in plants subjected to foliar spray with SA 0.5 mM (T2). The mature dark green oven dried spikes were analysed for carbohydrates, piperine, volatile oil and oleoresin content, which varied significantly among the different treatments. The treatment, T2 recorded significantly higher carbohydrate, starch and sugar contents. The same treatment reported the highest values with respect to piperine (1.15 per cent), volatile oil (1.32 per cent) and oleoresin (14.21 per cent) content. This treatment gave approximately 30 per cent increase in piperine content, 12 per cent increase in volatile oil and oleoresin content over the control. However, at higher concentration of SA, T6 (SA 2.5 mM), piperine content (0.90 per cent) was found to be significantly lower and on par with foliar spray treatments devoid of SA. The physiological parameters at 3, 5 and 7 MAP, showed significant variation with regards to the foliar treatments. The foliar spray treatment with SA 0.1 mM (T1) recorded significantly higher values with respect to dry matter production, leaf area index, stomatal conductance and photosynthetic rate at all the stages of observation. The physiological parameters viz., NAR, cell membrane stability index and proline recorded significantly higher values in T2 at all stages of observation. The yield parameters viz., number of spikes, fresh and dry spike yield, fresh and dry root yield and root length varied significantly with different foliar spray treatments. With respect to number of spikes (177.33), fresh (133.88 g) and dry (25.81 g) spike yield, T1 recorded significantly higher values. T1 was found to be on par with T2 with respect to dry spike yield. The root parameters such as fresh (30.15 g) and dry (12.15 g) root yield and root length (70.61 cm) were significantly higher in treatment T2. With regards to dry root yield, T2 was found to be on par with T1. However, harvest index, spike length, spike girth and driage did not showed any significant variation among the treatments. The nutrient uptake by the crop was studied and the results revealed that the plants exposed to T1 showed significantly higher uptake of N (1.27 g plant-1). However, with respect to P (0.059 g plant-1) and K (1.78 g plant-1), treatment T2 recorded higher values. In the study, it was observed that SA 0.1 mM (T1) gave better performance with respect to plant growth parameters and physiological parameters followed by SA 0.5 mM (T2). Foliar spray with SA 0.5 mM gave superior performance with respect to plant metabolites, while high spike and root yield were recorded in foliar spray with SA 0.1 mM and 0.5 mM. Hence, it can be inferred from the study that foliar spray with either concentration of SA 0.1 mM and 0.5 mM. at 2, 4 and 6 MAP could effectively elicit plant growth, yield and metabolite production in Piper longum.